Polymorphisms of xenobiotic metabolizing enzymes in bladder cancer patients of the Semmelweis University Budapest, Hungary. Issue 7 (18th April 2017) - Ebbinghaus, Dörte; Bánfi, Gergely; Selinski, Silvia; Blaszkewicz, Meinolf; Bürger, Hannah; Hengstler, Jan G.; Nyirády, Péter; Golka, Klaus
ABSTRACT: Polymorphic xenobiotic metabolizing enzymes such as N-acetyltransferase 2 (NAT2) or glutathione S-transferase M1 (GSTM1) are known to modulate bladder cancer risk. As no apparent data were available from Hungary, a former member of the eastern European economic organization, a study was performed in Budapest. In total, 182 bladder cancer cases and 78 cancer-free controls were investigated by questionnaire. Genotypes of NAT2, GSTM1, GSTT1, rs1058396 and rs17674580 were determined by standard methods. Current smokers' crude odds ratio (OR) (3.43) and former smokers crude OR (2.36) displayed a significantly increased bladder cancer risk. The risk rose by a factor of 1.56 per 10 pack years. Exposure to fumes was associated with an elevated bladder cancer risk (23% cases, 13% controls). Sixty-four % of the cases and 59% of controls were slow NAT2 acetylators. It was not possible to establish a particular impact of NAT2*6A and *7B genotypes (15 cases, 8%, 5 controls, 7%). GSTT1 exerted no marked influence on bladder cancer (negative 21% cases vs. 22% controls). The portion of GSTM1 negative bladder cancer patients was increased (63% cases vs. 54% controls). The SLC14A1 SNPs rs1058396[AG/GG] and the nearby rs17674580[CT/TT] occurred more frequently in cases (79% and 68%) than controls (77% and 55%). The portion of GSTM1 negative bladder cancer patients is comparable with portions reported from other industrialized areas like Lutherstadt Wittenberg/Germany (58%), Dortmund/Germany (70%), Brescia/Italy (66%) or an occupational case-control series in Germany (56%). Data indicate that GSTM1 is a susceptibility factor for environmentally triggered bladder cancer rather than for smoking-mediated bladder cancer.